EDUKASI ETIKA DIGITAL ISLAMI MENJADI BIJAK MUSLIM DI ERA MEDIA SOSIAL DI SMP MUHAMADIYAH 3 KOTA SEMARANG - Rico Setyo Nugroho, Rico Setyo Nugroho (Komunikasi, 2025)
The rapid development of social media has made Generation Z strongly attached to the digital world. This condition presents both opportunities and challenges, especially for junior high school students who are still in the process of character formation. Islamic values need to be integrated into social media use so that students can become wise users. Based on this issue, the team conducted a Community Service Program (PKM) at SMP Muhammadiyah 3 Semarang on June 27, 2025, coinciding with 1 Muharram 1447 H (Islamic New Year). This momentum was chosen because it is rich in meaning of hijrah, introspection, and new resolutions, which align with the program's goal of promoting digital hijrah. The method involved socialization with the principal, teachers, and the school committee, followed by interactive seminars and workshops for students. The materials focused on Islamic digital ethics, self-control in using social media, and the Prophet Muhammad's exemplary communication practices. The results showed high enthusiasm from students who actively engaged in discussions, teachers' awareness of their role as digital role models, and parents gaining new insights into guiding their children. The discussions also produced an agreement to draft an Islamic digital ethics guideline for the school. In conclusion, this PKM effectively raised awareness of the importance of Islamic digital ethics in the social media era. The recommendation is to sustain the program through follow-up workshops, strengthening school–parent collaboration, and involving the student council (OSIS) as agents of positive change.